Peningkatan kualitas pengusaha ultra mikro melalui pelatihan Canva di Kabupaten Ngawi - Niken, Niken Nafiatu Rahma; Devi, Heidy Paramitha (Nur Science Institute, 2023)
Design creativity plays a vital role in the success of ultra-micro businesses. One of them is success in creating a design that suits the business and attracts buyers' interest. One example of a tool for creating designs is using the Canva application. The problem encountered by ultra-micro entrepreneurs in the Ngawi area is that they need to gain skills to provide product information for their business. Therefore, training and assistance are needed to use the Canva application to develop their business. The objectives of this service activity are: (1) increasing the graphic design skills of ultra-micro business actors in the success of their business and (2) increasing consumer interest with the availability of business identities through attractive designs. The methods used in carrying out this activity are initial observation, delivery of material, and practical implementation of Canva. The result of this activity was the implementation of training on using the Canva application with 10 participants who could take part in the training until the end of the event. The participants learned about using the Canva application to improve the quality of ultramicro entrepreneurs and the design skills of business actors.